Brass alloys improved with antimony additives for gamma-ray shielding applications - Levet, Aytac; Kaur, Parminder; Kahruman, Cem; Thakur, Sonika; Buyukyildiz, Mehmet (Pergamon-Elsevier Science Ltd, 2026)
In the present research, brass alloys (Cu-63, Zn-37) have been modified with antimony content ranging from 0 to 5 % to enhance their radiation resistance. Comprehensive analyses were conducted to evaluate the effects of antimony doping on both the microstructural and radiation attenuation characteristics of these alloys. Phase diagrams and microstructural analysis revealed dendritic structures and Sb accumulation at grain boundaries at higher concentrations. The crucial radiation shielding parameters, including mass attenuation coefficient (MAC), effective atomic number (Zeff), effective electron density (Neff), half-value layer (HVL), and mean free path (MFP), were investigated both experimentally and theoretically across photon energies ranging from 81 to 383.9 keV. Results show that increasing antimony content enhances radiation absorption, with the 5 % Sb alloy demonstrating the highest shielding effectiveness. The MAC of the A6 brass alloy containing 5 % Sb showed a 15.5 % increase relative to the standard A1 brass alloy at 81 keV. These findings suggest that antimony-doped brass alloys can serve as effective, non-toxic alternatives for radiation shielding in nuclear, medical, and industrial applications.
Keywords: Antimony-doped brass; Gamma-ray shielding; Microstructural analysis; Photon interaction parameters